A review on present condition, problems and prospect of beef cattle production: Bangladesh perspective: Present condition of beef cattle production in Bangladesh - Mahbubul, M; Huda, M N; Akter, M M; Ety, M U S (Bangladesh Journal of Animal Science, 2025)
The economic development of Bangladesh has provided an opportunity for beef production to meet its increasing demand. With the rise in income level and change in dietary habits of Bangladeshi people, beef fattening is expected to become more popular in the coming years. Cattle fattening has not yet been established as an industry in the country, but due to market prospects of beef, beef cattle fattening may be an important sector both in terms of income generation, employment, and food security. Little information is available on beef cattle production in Bangladesh. This review is going to focus on the existing beef cattle production system, its challenges, and prospects in the Bangladesh context. Bangladesh Journal of Animal Science 54(1): 1-11, 2025